MicroRNA signatures predict dysregulated vitamin D receptor and calcium pathways status in limb girdle muscle dystrophies (LGMD) 2A/2B. (August 2016) - Aguennouz, M.; Lo Giudice, C.; Licata, N.; Rodolico, C.; Musumeci, O.; Fanin, M.; Migliorato, A.; Ragusa, M.; Macaione, V.; Di Giorgio, R. M.; Angelini, C.; Toscano, A.
Abstract : miRNA expression profile and predicted pathways involved in selected limb‐girdle muscular dystrophy (LGMD)2A/2B patients were investigated. A total of 187 miRNAs were dysregulated in all patients, with six miRNAs showing opposite regulation in LGMD2A versus LGMD2B patients. Silico analysis evidence: (1) a cluster of the dysregulated miRNAs resulted primarily involved in inflammation and calcium metabolism, and (2) two genes predicted as controlled by calcium‐assigned miRNAs (Vitamin D Receptor gene and Guanine Nucleotide Binding protein beta polypeptide 1gene) showed an evident upregulation in LGMD2B patients, in accordance with miRNA levels. Our data support alterations in calcium pathway status in LGMD 2A/B, suggesting myofibre calcium imbalance as a potential therapeutic target. Copyright © 2016 John Wiley & Sons, Ltd.